2013
DOI: 10.1371/journal.pone.0070303
|View full text |Cite
|
Sign up to set email alerts
|

Gene Silencing of Porcine MUC13 and ITGB5: Candidate Genes towards Escherichia coli F4ac Adhesion

Abstract: BackgroundIntegrin beta-5 (ITGB5) and mucin 13 (MUC13) genes are highly expressed on the apical surface of intestinal epithelia and are thought to be candidate genes for controlling the expression of the receptor for enterotoxigenic Escherichia coli (ETEC) F4ac. Human MUC13 protein has an expected role in protecting intestinal mucosal surfaces and porcine ITGB5 is a newly identified potential receptor for ETEC F4ac.Methodology/Principal FindingsTo test the hypothesis that ITGB5 and MUC13 both play key roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
(66 reference statements)
1
10
0
Order By: Relevance
“…The most striking result found here was the strong positive effect of PGM. While other fimbriae, including F5 expressed by porcine ETEC, may adhere to decoy ligands present in mucin [ 42 ], PGM did not inhibit CFA/I mediated MRHA. Of note, the positive effect of PGM was observed despite previous sterilization by autoclaving, indicating that the original structures of the large, complex glycoproteins found in mucin were not critical to the induction of CFA/I surface expression.…”
Section: Resultsmentioning
confidence: 99%
“…The most striking result found here was the strong positive effect of PGM. While other fimbriae, including F5 expressed by porcine ETEC, may adhere to decoy ligands present in mucin [ 42 ], PGM did not inhibit CFA/I mediated MRHA. Of note, the positive effect of PGM was observed despite previous sterilization by autoclaving, indicating that the original structures of the large, complex glycoproteins found in mucin were not critical to the induction of CFA/I surface expression.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic Lactobacillus strains can also upregulate the expression of transmembrane MUC3, and these bacteria induce release of the MUC3 extracellular domain [76]. Transmembrane MUC13 prevents ETEC adhesion in pigs [77] and a MUC13 isoform lacking the glycosylated extracellular domain is associated with an increased susceptibility to ETEC [78]. However, some evidence has been published to suggest that, rather than MUC13, it is a neighboring gene region that is involved in the reported ETEC susceptibility [79].…”
Section: Barrier Function Mucosal Maintenance and Interactions Withmentioning
confidence: 99%
“…Polymorphisms in intron 7 of the MUC4 gene have been used to classify an important percentage of piglets as susceptible or resistant to F4 ETEC [ 16 , 17 ]. Although Ren et al and Zhou et al both found that susceptibility/resistance toward ETEC F4ac is conferred by the MUC13 gene in pigs, Schroyen et al reported that MUC13 and MUC20 gene expression are not related to ETEC F4ac susceptibility in piglets, and Goetstouwer et al recently confirmed that MUC4 and MUC13 are not completely associated with F4ab/ac ETEC susceptibility [ 10 , 11 , 13 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various potential host receptors for F4 fimbriae have been described, including MUC4, MUC13, MUC20, ITGB5, and TFRC [ 10 13 ]. The polymorphic Xba I restriction enzyme site in intron 7 of the muc4 gene has been used as a biomarker to classify an important percentage of piglets as susceptible or resistant to F4 + ETEC infections [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%